Analisis Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Praktik Pemeliharaan Chassis dan Pemindah Tenaga Teknik Kendaraan Ringan (TKR) SMK Cendana DDI Samarinda - Mawarda Nurodanika; Prengky (CENDIKIA, 2025)
Vocational education institutions are required to implement Occupational Safety and Health (OSH) standards to ensure the protection of students during practical learning activities. This study aimed to analyze OSH facilities, potential workplace accidents, and preventive measures in the chassis and powertrain maintenance workshop of the Automotive Engineering (TKR) program at SMK Cendana DDI Samarinda. A mixed-method approach with a case study design was employed. Data were collected through observation, questionnaires, in-depth interviews, and documentation. The findings indicate that OSH facilities were generally available, including Personal Protective Equipment (PPE) such as head, foot, eye, face, hand, and respiratory protection, as well as protective clothing. However, ear protection and fire extinguishers were insufficiently provided. The highest potential workplace accident identified was electrical shock (34.10%), while the most significant impact was material loss (35.80%). Preventive efforts were reflected in proper preparation before practical activities (35.80%) and safe behavior during practice implementation (66.60%).